Wave propagation in a volleyball game ball: finite element and mathematical simulation - Shen, G.; Fan, Y. (Waves in Random and Complex Media, 2023)
In the current work, for the first time, with the aid of mathematical and finite element modeling of a spherical shell, wave propagation in the volleyball game ball under external loading is presented. A multi-physics simulation based on mathematical modeling and a finite element approach for modeling the current volleyball game ball is presented. Hamilton`s principle and spherical shell coordinate are coupled for obtaining the governing equations of the volleyball game ball under internal loading. By using the generalized differential quadrature (GDQ) method and analytical method, the governing equations of the volleyball game ball are solved. Finally, the results show that the ball`s radius has a key role in the dynamic stability of the volleyball game ball. One of the important outcomes of the current research is that, unlike the ball`s size, heavier balls tend to be more stable when they hit the ground. The outputs of the current work can be used for future analysis of the volleyball game ball for improving its stability.